POLITIK MULTIKULTIKULTURALISME DALAM NOVEL KANCING YANG TERLEPAS KARYA HANDRI T.M. - WISNU MURTI, INDRA; Eko Retnosari, Ira (Universitas PGRI Adi Buana Surabaya, 2019)
One of literature form that can be examined related to the results of what the authorwanted to tell is a novel. The novel chosen in this study was Kancing yang Terlepas byHandry T.M. This novel is interesting because it was written by a Semarang writer